2017
DOI: 10.1007/s12640-017-9700-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Production in the Striatum and Cerebellum of a Rat Model of Preterm Global Perinatal Asphyxia

Abstract: Encephalopathy due to perinatal asphyxia (PA) is a major cause of neonatal morbidity and mortality in the period around birth. Preterm infants are especially at risk for cognitive, attention and motor impairments. Therapy for this subgroup is limited to supportive care, and new targets are thus urgently needed. Post-asphyxic excitotoxicity is partially mediated by excessive nitric oxide (NO) release. The aims of this study were to determine the timing and distribution of nitric oxide (NO) production after glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…This could reduce even further the inhibitory capacity of the striatum and increase the effect of dopamine in the structure worsening the symptoms of dyskinesia and psychosis. This point of view, is supported by previous works where PA produced an increase in the number of cells labeled using antibodies against neuronal nitric oxide synthase and cyclic guanosine monophosphate in the striatum (Barkhuizen, Van De Berg, et al, 2017). This is consistent with previous related research in the same model of asphyxia, where an increased striatal cGMP production was found at P10 (Loidl et al, 1998).…”
Section: Increase In Calretinin Neun and Dapisupporting
confidence: 91%
“…This could reduce even further the inhibitory capacity of the striatum and increase the effect of dopamine in the structure worsening the symptoms of dyskinesia and psychosis. This point of view, is supported by previous works where PA produced an increase in the number of cells labeled using antibodies against neuronal nitric oxide synthase and cyclic guanosine monophosphate in the striatum (Barkhuizen, Van De Berg, et al, 2017). This is consistent with previous related research in the same model of asphyxia, where an increased striatal cGMP production was found at P10 (Loidl et al, 1998).…”
Section: Increase In Calretinin Neun and Dapisupporting
confidence: 91%
“…In this context, studies using preterm animal models could be useful to increase our knowledge of the state of prematurity, and to explore new insights in the field of nutritional interventions in preterm neonates in order to counteract immunodeficiencies. To date, there are few preterm models in rodents, and most of these are only focused on the impact of prematurity on brain [16] or lung development [17] or NEC [18,19], but none study immune system maturation, which is especially affected in prematurity. To our knowledge, the only premature animal model studying immunity was performed in pigs [20].…”
Section: Introductionmentioning
confidence: 99%
“…Following an acute ischemic insult in term infants, the deep grey nuclei are commonly involved [ 11 ]. This is ascribable to the presence of NOS-expressing striatal neurons, that are relatively resistant to hypoxia-ischemia injury and glutamate excitotoxicity [ 18 ] and, in response to the ischemic event, produce excessive amounts of RNS [ 19 ], exerting extensive nitrosative effects on the adjacent neural structures and thus further contributing to their damage.…”
Section: Pathophysiological Mechanisms Of Oxidative Brain Damagementioning
confidence: 99%